Novel CCI-OTA-Based Grounded Capacitor Current-Mode Biquadratic Bandpass and Lowpass Filters - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A novel current-mode active filter topology using a first generation current conveyor (CCI) and an operational transconductance amplifier (OTA) is presented. Using this topology, grounded-capacitor biquadratic bandpass and lowpass filter sections, with at most five one-port passive elements, are realized. In these realizations, the parameter ω0 can be adjusted without disturbing the parameter ω0/ Q0